1987
DOI: 10.1038/ki.1987.83
|View full text |Cite
|
Sign up to set email alerts
|

Evidence against increased glomerular pressure initiating diabetic nephropathy

Abstract: Studies were carried out to determine whether exaggerated glomerular hydraulic pressure (PG) initiates the development of glomerular pathology and proteinuria in insulin-dependent diabetic rats. Normotensive (WKY) and hypertensive rats (SHR) were made diabetic by streptozotocin injection. One group of SHR diabetic rats was treated with antihypertensive drugs to reduce blood pressure. One week after onset of diabetes, micropuncture determinations of PG, measured by stopped-flow technique, revealed that PG was h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(29 citation statements)
references
References 20 publications
2
26
1
Order By: Relevance
“…In both studies the SHR rats were hypertensive compared to the WKY rats. In one study [23] no difference was found between SHR and WKY rats with regard to the development of diabetic nephropathy. In the other study [24] the rats were followed for 8 months after the induction of diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both studies the SHR rats were hypertensive compared to the WKY rats. In one study [23] no difference was found between SHR and WKY rats with regard to the development of diabetic nephropathy. In the other study [24] the rats were followed for 8 months after the induction of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our model, diabetes induced in DS rats resulted in a rapid development of glomerulopathy mostly characterised by mesangial expansion typical of the advanced phase of diabetic nephropathy. The relationship between hypertension and changes in kidney function and morphology in rats with streptozotocin-induced diabetes has previously been evaluated in two studies on spontaneously hypertensive rats (SHR) [23,24]. The SHR rats are considered to be salt-insensitive.…”
Section: Discussionmentioning
confidence: 99%
“…38 - 39 However, micropuncture studies have shown that lowering the blood pressure to normotensive levels in diabetic SHR afforded protection against the development of early diabetic glomerulopathy independently of a reduction in glomerular hydraulic pressure. 40 Angiotensin II has many other actions within the kidney, including effects on mesangial cell contraction and macromolecular uptake through the mesangium, 41 tubular sodium reabsorption, 42 and vasa recta blood flow, 43 all of which might modulate the progression of intrarenal pathology in renal failure. Renal ACE is not influenced by changes in salt balance 22 -44 and is effectively inhibited by ACE inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…on the progression of glomerular sclerosis without affecting candidate pathophysiologic mechanisms. Such data were extrapolated into a general scheme of pathophysiology applied to all forms of glomerular sclerosis by taking data as evidence against the importance of such mechanisms in question (40)(41)(42)(43)(44). In this regard, our data showing the unique susceptibility of young remnant glomeruli to sclerosis despite glomerular pressure and size comparable to or even below adult levels point to the significance of host-dependent factors as an important determinant for the progression of glomerular sclerosis, which may potentially be altered by these experimental maneuver^.^ Of note, the notion has been widely accepted in recent years that local or systemic growth factors that promote glomerular hypertrophy may underlie the development and progression of glomerular sclerosis.…”
Section: Discussionmentioning
confidence: 99%